Effects of potentised homeopathic medicines on the germination, growth and photosynthetic activity of Pisum sativum L. - Panda, Swati S; Mohanty, Swati S; Dhal, Nabin K (Recent Research in Science and Technology, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]–> The present study evaluates the possible effect of potentised homeopathic medicine, Arsenicum album and Baryta carbonica on germination, growth and photosynthetic activity of pea seedlings (Pisum sativum L.). The seedlings of pea were treated with three different centesimal potencies (8CH, 32CH, 202CH) of both the medicine. With the increase in potency, the morphological parameters viz. length of plumule and radical increased. The photosynthetic pigments (chlorophyll, carotinoids, and pheophytin) also showed the similar result. Hence, a stimulating effect was observed on growth as well as photosynthetic activity at the higher potency as compared to untreated one even after the dilution of drug beyond the Avogadro’s number.